2023
DOI: 10.3390/toxics11030262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shellfish and Organic Fertilizer Amendments on Soil Nutrients and Tea Yield and Quality

Abstract: Soil acidification in tea plantations leads to an excessive heavy metal content in tea, decreasing its yield and quality. How to apply shellfish and organic fertilizers to improve soil and ensure the safe production of tea is still not clear. A two-year field experiment was conducted in tea plantations in which the soil was characterized by a pH of 4.16 and concentrations of lead (Pb) (85.28 mg/kg) and cadmium (Cd) (0.43 mg/kg) exceeding the standard. We used shellfish amendments (750, 1500, 2250 kg/ha) and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…At the feto-maternal interface, physiologic regulation of trophoblast differentiation is vital to the establishment of a normal placental architecture while dysregulation of this process, either due to the abnormal expression of some genes or the presence of a xenobiotic, induces placental abnormalities to affect pregnancy (Gong et al, 2021; Mohamad et al, 2020; Rosenfeld, 2021; Wu et al, 2023). In this study, we found that BPS did not induce noticeable defects in the expression of the EVT marker genes and EVT morphology.…”
Section: Discussionmentioning
confidence: 99%
“…At the feto-maternal interface, physiologic regulation of trophoblast differentiation is vital to the establishment of a normal placental architecture while dysregulation of this process, either due to the abnormal expression of some genes or the presence of a xenobiotic, induces placental abnormalities to affect pregnancy (Gong et al, 2021; Mohamad et al, 2020; Rosenfeld, 2021; Wu et al, 2023). In this study, we found that BPS did not induce noticeable defects in the expression of the EVT marker genes and EVT morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Five soil samples were obtained, parts of which were bagged, sealed, and stored at 4 • C, while the other parts were naturally dried, ground, and sieved for use in soil indicator assays. In brief, the total nitrogen content was determined using a Kazitometer [22], and P, K, Ca, and Mg contents were determined using inductively coupled plasma-atomic emission spectrometry (ICP-AES). Soil alkali nitrogen content was determined using the alkali diffusion method; soil available phosphorus content and available potassium content were determined using the molybdenum-antimony resistance method and the flame light method [22].…”
Section: Test Designmentioning
confidence: 99%
“…In brief, the total nitrogen content was determined using a Kazitometer [22], and P, K, Ca, and Mg contents were determined using inductively coupled plasma-atomic emission spectrometry (ICP-AES). Soil alkali nitrogen content was determined using the alkali diffusion method; soil available phosphorus content and available potassium content were determined using the molybdenum-antimony resistance method and the flame light method [22]. Soil nitrate nitrogen content was determined using nitrosalicylic acid, and ammonium nitrogen content was determined using indophenol blue [23].…”
Section: Test Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The certain range of Al 3+ caused remarkable growth and physicochemical improvements in different tea varieties [ 129 ]. The application of shellfish amendments in acidified tea plantations could contribute to a certain degree to the yield, quality and economic value of tea leaves [ 130 ]. Although the understanding of tea plants under the influence of Al was still extremely limited, breeders were now further dissecting the mechanisms of Al tolerance and utilization in tea plants, thus setting the foundation for optimizing acidic tea plantations, optimizing the yield quality of tea plants and breeding acid-tolerant crops for the future [ 131 ].…”
Section: Major Directions and Measures For Tea Plants Breedingmentioning
confidence: 99%